The Distribution of Zeroes and Critical Points of Solutions of a Second Order Half-Linear Differential Equation - Pedro Almenar; Lucas Jódar (Abstract and Applied Analysis)
This paper reuses an idea first devised by Kwong to obtain upper bounds for the distance between a zero and an adjacent critical point of a solution of the second order half-linear differential equation (p(x)Φ(y'))'+q(x)Φ(y)=0, with p(x),q(x)>0, Φ(t)=|t|r-2t, and r real such that r>1. It also compares it with other methods developed by the authors.